2013
DOI: 10.1080/09670262.2013.844860
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and systematics of Calliblepharis hypneoides, sp. nov. (Cystocloniaceae, Rhodophyta) from the Atlantic Iberian Peninsula

Abstract: Calliblepharis hypneoides Díaz-Tapia, Bárbara & Hommersand, sp. nov., is described based on plants collected in sand-covered rocks from southern France to Portugal. Calliblepharis hypneoides is distinguished by a terete thallus, forming an extensive basal system of entangled prostrate axes that bear few irregularly branched upright axes, an inner structure consisting of a central axial filament surrounded by 5-7 filaments of elongated cells, a continuous outer cortex, spermatangial parent cells transformed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Several recent taxonomic studies of molecular phylogeny with attention paid to female morphology indicated that the developmental patterns of carposporophytes are a proper character for defining boundaries at the generic level in the orders Gigartinales and Halymeniales, as well as Ceramiales (Lin et al 2002, 2012, Díaz-Tapia et al 2013, Gargiulo et al 2013). In our phylogenetic trees (Figures 55 and 56), the original concept of the Myriogramme-group by Kylin (1924) is first divided by procarp shape (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent taxonomic studies of molecular phylogeny with attention paid to female morphology indicated that the developmental patterns of carposporophytes are a proper character for defining boundaries at the generic level in the orders Gigartinales and Halymeniales, as well as Ceramiales (Lin et al 2002, 2012, Díaz-Tapia et al 2013, Gargiulo et al 2013). In our phylogenetic trees (Figures 55 and 56), the original concept of the Myriogramme-group by Kylin (1924) is first divided by procarp shape (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Section samples were stained with 1% aniline blue, acidified with 1% HCl and mounted in a 40% corn syrup solution. We also treated with Wittmann's (1965) aceto-iron-hematoxylin-chloral hydrate, and mounted in 50% Hoyer's mounting medium (Lin et Calderon and Boo 2016, Won et al 2016, Yang and Kim 2016, reproductive structures have remained important diagnostic characteristics for differentiating many genera in the order Gigartinales (Hommersand et al 1999, Díaz-Tapia et al 2013. For instance, Hypnea and Calliblepharis can be readily distinguished each other by female reproductive structures even if they share many vegetative features in common.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…For example, current classification of H. saidana lack the consideration of reproductive structure, according to Shin and Boo (1994) which is essential for proper reassessment due to its similarity to Calliblepharis in terms of vegetative features, i.e., complanate thalli, dispersed surface cells, and numerous pit connections between medullary cells. In addition, recently described taxa, Calliblepharis hypneoides Díaz-Tapia, Bárbara & Hommersand and C. psammophilus D'Archino & W. A. Nelson, were assigned to Calliblepharis based on observations of the female structures even though they superficially resembled the species of Hypnea (Díaz-Tapia et al 2013, D'Archino et al 2015.…”
Section: Specimen Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Intertidal sand-covered rocks are other common, more accessible, but often poorly explored habitat. The presence of sediments in intertidal rocks negatively affects many benthic organisms, and sand-covered rocks host a particular algal assemblage (Airoldi 2003, Díaz-Tapia et al 2013a in which several new red algal species have been recently described (Díaz-Tapia and , Díaz-Tapia et al 2013b, D´Archino et al 2015. During our surveys of marine red algae in this habitat along the coasts of Espírito Santo and Rio de Janeiro (southeastern Brazil), we found abundant populations of a rhodomelacean species consisting of large plants (up to 25 cm in length) with seven pericentral cells and a dense cortication from close to the apices.…”
Section: Introductionmentioning
confidence: 99%